Frequency of Hyperthyroidism in patients of Atrial Fibrillation - Ammar Arshad, Ch Adnan Ahmed Ather, Sohail Bashir Sulehria, Saadia Choudhary, Maria Rehman, Zara Mehmood, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To find the frequency of hyperthyroidism in patients of atrial fibrillation admitted in Mayo hospital Lahore. Study setting: The study was conducted at Emergency Department, Cardiology Department and Department of Internal Medicine in Mayo Hospital Lahore\ Duration of study: It was from May 20, 2019 to November 20, 2019. Study design: It was Cross-Sectional study\ Methods: patients suffering with atrial fibrillation fulfilling the operational definition and inclusion criteria were enrolled. After aseptic measures, blood sample of 5 ml was drawn from left cubital vein with low sucking pressure. Sample was deposited to Center for Nuclear Medicine (CENUM) Laboratory at Mayo Hospital Lahore for thyroid function tests. Serum Thyroid Stimulating Hormone, Thyroxine and Triiodothyronine levels were noted and hyperthyroidism labeled as per the operational definition. Data was collected by the researcher himself noted on a specially designed proforma and presented in the form of tables and diagrams. Results: The mean value of age in our study was 55.13±14.01 year. In our study 40(42.6%) patients had hyperthyroidism. Conclusion: High frequency of hyperthyroidism in our study, suggests that routine thyroid function tests using sensitive thyroid-stimulating hormone assay with free T4 & free T3 levels is required in all those with acute atrial fibrillation. Keywords: Hyperthyroidism, Atrial Fibrillation.